IMPLEMENTASI MANAJEMEN KESISWAAN DALAM PEMBENTUKAN KARAKTER SISWA - Tatang Heri (Universitas Majalengka, 2021)
The research was motivated by the phenomenon of the character of SMAN 1 Kasokandel students not yet forming, presumably due to the implementation of student management that was not optimal. The research aims to: a) Know the implementation of student management; b) Knowing the supporting factors for the implementation of student management; c) Knowing the inhibiting factors of student management implementation: d) Knowing the principal's efforts in overcoming obstacles. This research uses a qualitative approach with analytical methods. The main data collection techniques and tools used in-depth interviews with the information determined purposively. Data were analyzed descriptively descriptively through data reduction, data presentation, and withdrawal. The validity data were tested through triangulation techniques. The results showed: a) Student management has been implemented properly; b) Implementation of student management which is supported by a religious environment, solid cooperation and harmony among student organizations; c) Implementation of student management is hampered by limited funds; d) To overcome obstacles, the principal has made good efforts through re-planning, coordinating with school committees and deliberations. In conclusion, student management has been implemented properly and has a positive impact on character ordering of SMA Negeri 1 Kasokandel students